Relationship between Organizational Justice and Nurses' Psychological Empowerment - H Zahednezhad; H Manoochehri; M Zaghari Tafreshi; P Farokhnezhad Afshar; R Ghanei Gheshlagh (Iran University of Medical Sciences, 2015)
Abstract Background & Aim: Individuals' perception of organizational justice is very important. The aim of this study was to identify the relationship between organizational justice and psychological empowerment of nurses working in hospitals affiliated to Shahid Beheshti University of Medical Sciences. Material & Methods: It was a descriptive- correlational study. The sample consisted of 155 nurses working in hospitals affiliated to Shahid Beheshti University of Medical Sciences who were recruited by random stratified sampling during 2012. Data was collected by Niehooff and Moorman's Organizational Justice questionnaire and Spreitzer's Psychological Empowerment instrument and analyzed by descriptive statistics, Pearson correlation coefficient and multiple regression using SPSS-PC (v. 16). Results: A significant positive correlation was found between organizational justice and nurses' psychological empowerment (p= 0.005). Also the results of multiple regression showed that interactional justice can explain %53 of the variance of Psychological empowerment of nurses. Conclusion: Regarding the significant relationship between organizational justice and nurses' psychological empowerment, managers' attention to organizational justice of healthcare system to improve the nurses' psychological empowerment is suggested.